Do the eyes have it? Using eye tracking to assess students cognitive dimensions - Nisiforou, Efi; Laghos, Andrew (My University, 2013)
Field dependence/independence (FD/FI) is a significant dimension of cognitive styles. The paper presents results of a study that seeks to identify individuals' level of field independence during visual stimulus tasks processing. Specifically, it examined the relationship between the Hidden Figure Test (HFT) scores and the eye tracking metrics. Moreover, it explored whether differences exist among the cognitive groups, in terms of the time taken to complete the given tasks. A sample of 16 PhD students recruited from a Public University in Cyprus was classified into Field-Dependent, Field-Independent and Field-Neutral learners. Data were collected and analysed through the use of eye tracking and SPSS statistics. Results revealed a statistical significant correlation between the scores retrieved from the HFT and the Eye tracker. Additionally, the FD and the FI groups differ with respect to the tasks time completion. The findings revealed the potential of eye tracking to be used as a tool in assessing users' cognitive traits. Finally, the vision of further agenda and some practical implications for instructional designers and educators are addressed.
Keywords: Cognitive abilities; Field dependence/independence; Eye tracking; Visual stimuli; Hidden figures test; Higher education